The Interventions for Sleep Disorders in Children with Attention Deficit and Hyperactivity Disorder: A Narrative Review - Pratiwi, Risma Dwi Nur; Fitri, Siti Yuyun Rahayu; Mulya, Adelse Prima (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Attention deficit and hyperactivity disorder (ADHD) is the most common neurodevelopmental disorder in childhood. Children with ADHD have more frequent comorbid sleep disorders than healthy children. The current methods of treating sleep disorders in ADHD children are still focused on pharmacological interventions which in fact only provide little benefit. AIM: This study aims to identify existing studies regarding the types of nonpharmacological and complementary interventions for sleep disorders in children with ADHD using a narrative review approach. METHODS: This was a narrative review. Inclusion criteria included articles in English and Bahasa, full-text articles, primary studies, and children with ADHD aged 18 years with or without comorbidities as the research sample, and the article having been published in the last 10 years. Searches were performed in several databases: PubMed, Springer, Web of Science, and Google Scholar. RESULTS: The result showed that programs for managing sleep disorder in ADHD are behavioral therapy, behavioral parent training (BPT), behavioral sleep intervention, neurofeedback, mind-body therapy, L-theanine supplementation, horse milk supplementation, and play therapy. The programs are found to be effective in improving sleep. CONCLUSION: The program most comprehensive with a high level of ease of implementation was BPT.